Dari Limbah Menjadi Harapan : Gerakan Ecobrick KKN UNP Wujudkan Kudu Gantiang Barat Bersih dan Berdaya - Fatmawati, Riya; Wizandri, Ahmad Dhaniel; Saputri, Mira Tiara; Azzahra, Putri; Fadhilah, Salma; Rahima, Zakiya (CV. ITTC INDONESIA, 2025)
Plastic waste management in Nagari Kudu Gantiang Barat has become an increasingly complex environmental problem due to limited waste processing facilities, a lack of public awareness of the dangers of plastic waste, and the widespread practice of indiscriminate waste disposal. This situation has resulted in increased environmental pollution, declining health, the erosion of village aesthetics, and a weakening of collective awareness of maintaining environmental cleanliness. Therefore, efforts are needed that directly involve the community and provide simple, easy-to-implement solutions to reduce plastic waste. This study aims to implement and evaluate the effectiveness of the ecobrick movement carried out by UNP KKN students as an alternative for managing plastic waste that is more environmentally friendly and can empower the community. The methods used included outreach activities, technical training, household plastic waste collection, and hands-on ecobrick-making practice with local residents. The analytical technique employed was qualitative descriptive analysis through observation, documentation, and evaluation of community involvement throughout the entire activity series. The research results showed that over two hundred ecobrick bottles were successfully produced and used as village boundary markers. This program raised community awareness about waste management, fostered a spirit of mutual cooperation, and opened up opportunities to utilize waste as a valuable alternative material. Overall, the ecobrick movement has proven feasible and can be replicated in other areas.